Disruption of the Golgi zone and inhibition of the conversion of proparathyroid hormone to parathyroid hormone in human parathyroid tissue by tris(hydroxymethyl)aminomethane - McGregor, DH; Chu, LL; MacGregor, RR; Cohn, DV (The American journal of pathology, 1977)
Tris(hydroxymethyl)aminomethane (Tris, Tromethamine, THAM) and other non-amphoteric amines were previously reported to inhibit the conversion of proparathyroid hormone to parathyroid hormone in bovine parathyroid glands incubated in vitro. This inhibition correlated with a striking dilation of the Golgi complex. This work has now been extended to normal, hyperplastic, and adenomatous parathyroid glands from human subjects. The tissues were incubated for up to 3 hours with 3H-leucine in physiologic solutions (control) or in the same solutions containing 50 mM Tris. In one case, diethylamine also was tested. Electron microscopy revealed that the amines produced a dilation of the Golgi complex and swelling of vesicles, predominantly in the region of the Golgi zone. Other organelles were normal in appearance. During the same period, Tris reduced by sixfold the ratio of the parathyroid hormone to proparathyroid hormone, from a control value of 2:1 to 1:3. It was apparent that Tris exerted the same biochemical and morphologic actions in human parathyroid tissues as it was previously shown to do in bovine glands. These studies support the concept that the Golgi zone is that region in the parathyroid gland in which proparathyroid hormone to parathyroid hormone conversion is initiated and that Tris inhibits this conversion through disruption of the converting site.